Assessment of knowledge, awareness and preventive measures of cervical cancer among female medical students (Bangladesh Journal of Medical Science, 2016)
Objectives: The main objective of the study to evaluate the knowledge about cervical cancer causes, vaccination and treatment among female medical students.Materials and Methods: It was a cross sectional study conducted in Melaka Manipal Medical College (Manipal campus), Manipal during October 2012 to April 2013. This study included 194 female medical students from MBBS and BDS undergraduate courses. Data were collected by using validated questionnaire. Data were analysed by SPSS 16 Software.Results The present results shows that the female students demonstrated good knowledge about cervical cancer, pap smear test, prevention and treatment. Among the respondents 97% had heard about cervical cancer, only 3% of female students had the family history of cervical cancer. However many students are did not know that smoking (34%), many child birth (40%) and usage of oral contraceptives (38%) are the risk factors for the cervical cancer.Conclusion: The present study shows adequate levels of knowledge and awareness about pap smear test, prevention and treatment of cervical cancer. Many of the students they did not have the adequate knowledge about risk factors of cervical cancer. This study indicates that further educational programs, especially about risk factors, needed in female medical students.Bangladesh Journal of Medical Science Vol.15(4) 2016 p.583-587